Evolution and revolution of imaging technologies in neurosurgery - Ogando-Rivas, Elizabeth; Castillo, Paul; Beltran, Jesus Q.; Arellano, Rodolfo; Galvan-Remigio, Isabel; Soto-Ulloa, Victor; Díaz-Peregrino, Roberto; Ochoa-Hernandez, Diana; Reyes-González, Pablo; Sayour, Elias; Mitchell, Duane (Neurologia medico-chirurgica, 2022)
We understand only a small fraction of the events happening in our brains; therefore, despite all the progress made thus far, a whole array of questions remains. Nonetheless, neurosurgeons invented new tools to circumvent the challenges that had plagued their predecessors. With the manufacturing boom of the 20th century, technological innovations blossomed enabling the neuroscientific community to study and operate upon the living brain in finer detail and with greater precision while avoiding harm to the nervous system. The purpose of this chronological review is to 1) raise awareness among future neurosurgeons about the latest advances in the field, 2) become familiar with innovations such as augmented reality (AR) that should be included in education given their ready applicability in surgical training, and 3) be comfortable with customizing these technologies to real-life cases like in the case of mixed reality.
Gesehen am 22.04.2024